APAKAH KEPEMILIKAN INSTITUSIONAL DAPAT MEMODERASI FAKTOR-FAKTOR YANG MEMPENGARUHI AGRESIVITAS PAJAK? - Amaliyah, Ahsanul; Nurdin, Fajar (Faculty of Economics and Business University of Mataram, 2024)
This research aims to analyze the impact of company size, political connections, profitability, and leverage on tax aggressiveness with institutional ownership as a moderator. This quantitative research is on manufacturing companies listed on the Indonesia Stock Exchange in 2020-2022. Sample collection used a purposive sampling approach. Data was obtained from the company's financial reports on the IDX and official websites. Data analysis uses panel data regression. The results show that company size, political connections, and leverage do not affect tax aggressiveness, while profitability affects tax aggressiveness. Institutional ownership can moderate profitability and leverage but not company size and political connections. This research aims to increase government efforts to prevent tax aggressiveness and increase taxpayer awareness.